Peran Masyarakat Dalam Kegiatan POSBINDU PTM Di Kelurahan Lumpur Kabupaten Gresik Tahun 2019: The Role of the Community in PTM POSBINDU Activities in the Mud Village, Gresik Regency in 2019 - Mashdariyah, Aistikhorotul; Rukanah, Rukanah (Universitas Muhammadiyah Sidoarjo, 2019)
The role of the community in Integrated Development Post activities or in Indonesia level with POSBINDU related to Non-Communicable Diseases (POSBINDU PTM) is a form of community participation in early detection, monitoring and early follow-up of risk factors for non-communicable diseases independently and continuously. This research to determine the relationship of characteristics (age, sex, occupational status, education level, level of knowledge and cadre support) with the role of the community in the Posbindu Non-communicable Disease (PTM) activity in the Kelurahan Lumpur District of Gresik. This research method uses quantitative analytic with cross sectional approach. The sample in this study was Posbindu participants in the Kelurahan Lumpur Kabupaten Gresik. Sample technique uses probability sampling with a sample size of 45 respondents. Data collection was carried out using a questionnaire. Data analysis was performed univariate, bivariate using the Chi-Square test. The results of statistical tests found a relationship between community roles and age (p = 0.003), level of knowledge (p = 0.038), and cadre support (p = 0.000). While there is no relationship between sex (p = 0.247), employment status (p = 0.094), and education level (p = 0.153) with the role of the community in Posbindu PTM activities in the Kelurahan Lumpur Kabupaten Gresik. The conclusion in this study is that there is a relationship between age, level of knowledge and support of cadres and the role of the community in Posbindu PTM activities in the Kelurahan Lumpur Kabupaten Gresik.